Smart Document-Centric Processing of Human Oriented Information Flows - Godlewska, Magdalena (Computing and Informatics, 2018)
Usually people prefer to focus on creative rather than repetitive and schematic work patterns. Still, they must spend a lot of time complying with the procedures, selecting the information they receive and repeatedly restoring the previous state of work. This paper proposes the Mobile INteractive Document architecture (MIND) - a document-centric uniform interface to provide both effective communication of content and coordination of activities performed on documents. MIND documents are proactive, capable of initiating process activities, interacting with individuals on their personal devices and migrating on their own between collaborators. Each MIND document is a mobile agent that has built-in migration policy to control its own workflow and services enabling proper processing of contained information. The architecture supports users in the implementation of procedures, and selection of services needed to work on the document. A Personal Document-Agent (PDA) is a further development of MIND aimed at preserving continuity of state of individuals' work to support their creativity and comfort of their daily work.